Correlation of CT Perfusion Parameters and Vascular Endothelial Growth Factor (VEGF) and Basic Fibroblast Growth Factor (BFGF) in Patients with Primary Liver Cancer. (24th May 2022) - Li, Xiao-min; Chen, Wei-bin; Zhang, Jing; Ma, Li-fang; Li, Qiang; Feng, Chao; Yuan, Xian-hua; Kang, Li-qing
Abstract : Objective. To investigate the correlation of CT perfusion-related parameters with serum vascular endothelial growth factor (VEGF) and basic fibroblast growth factor (BFGF) in patients with primary liver cancer. Methods . A total of 100 patients with primary liver cancer who were treated in our hospital from June 2019 to June 2021 were selected as the observation group, and 90 patients with benign liver lesions during the same period were selected as the control group. The CT perfusion-related parameters (perfusion volume and perfusion index) and serum VEGF and BFGF levels were compared between the two groups. Pearson correlation was used to analyze the correlation between CT perfusion-related parameters and serum VEGF and BFGF levels. Results . Compared to the control group, significantly higher HAP and lower HPP and TLP were observed in the observation group. The perfusion volume indexes of patients with different stages of liver cancer in the observation group were statistically different (P < 0.05 ). Compared to the control group, the observation group witnessed significantly higher HAPI and lower HPPI. There were statistically significant differences in the perfusion index of patients with different stages of primary liver cancer in the observation group (P < 0.05 ). The serum VEGF and BFGF levels in the observation group were significantly higher than those in the control group, and the serum VEGF and BFGF levels in patients with different stages of primary liver cancer in the observation group were statistically different (P < 0.05 ). Pearson correlation analysis showed that HAP and HAPI were positively correlated with VEGF and BFGF ( r = 0.986, P ≤ 0.001 ; r = 0.983, P ≤ 0.001 ), and HPP, TLP, and HPPI were negatively correlated with VEGF and BFGF ( r = −0.992, P ≤ 0.001 ; r = -0.993, P ≤ 0.001 ; r = −0.995, P ≤ 0.001 ). Conclusion . CT perfusion-related parameters and serum VEGF and BFGF levels in patients with primary liver cancer are abnormally expressed, and there is a strong correlation between the two, which might aid clinical diagnosis and treatment.